EFFECT OF TRINEXAPAC-ETHYL ON SUGARCANE VARIETIES - Lima, Sebastiao Ferreira de; Felix Alvarez, Rita de Cassia; Paiva Neto, Vespasiano Borges de; Simon, Catia Aparecida; Oliveira Andrade, Maria Gabriela de [UNESP] (Univ Federal Uberlandia, 2019)
Growth regulators have been widely employed as maturation inducers in the sugarcane crop, as an agricultural strategy. However, the response of varieties to the use of these compounds has been poorly studied, mainly in cerrado (savannah-like biome) areas occupied by the crop. This study was carried out to examine the effects of trinexapac-ethyl on important morphological characteristics of sugarcane varieties. The experiment was set up as a randomized block design with a 4 x 2 factorial arrangement consisting of four varieties (RB83-5054, SP80-1816, RB96-6928, and RB85-5156) associated or unassociated with application of trinexapac-ethyl (375 g L-1 of the a.i. ha(-1)), with four replicates. The ripener was applied at 126, 178, and 228 days after planting (DAP) the first-cycle sugarcane, using the dose of 125 g L-1 a.i. ha(-1) per application. Upon harvest, which occurred at 243 DAP, we determined the number of stalks per meter, weight of 30 stalks without top, internode length, number of internodes per stalk, and yield of sugarcane stalks. Ripener application increased the number of stalks in varieties RB96-6928 and RB83-5054 and the weight of 30 stalks in varieties RB96-6928 and RB83-5054 and SP80-1816; reduced internode length in varieties RB85-5156 and RB83-5054; and increased stalk yield per hectare in varieties RB96-6928 and RB83-5054, but did not increase the number of internodes per stalk in any of the tested varieties. The variables number of stalks, stalk weight, internode length, and stalk yield responded in a genotype-dependent manner to the application of trinexapac-ethyl.
Keywords: Ripeners; Moddus (R); Plant growth regulator; Saccharum spp